2021
DOI: 10.1186/s13059-021-02523-8
|View full text |Cite
|
Sign up to set email alerts
|

TAD-like single-cell domain structures exist on both active and inactive X chromosomes and persist under epigenetic perturbations

Abstract: Background Topologically associating domains (TADs) are important building blocks of three-dimensional genome architectures. The formation of TADs has been shown to depend on cohesin in a loop-extrusion mechanism. Recently, advances in an image-based spatial genomics technique known as chromatin tracing lead to the discovery of cohesin-independent TAD-like structures, also known as single-cell domains, which are highly variant self-interacting chromatin domains with boundaries that occasionally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 85 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…2, G to I). The radius of gyration is a metric that approximates the radial size of the chromosome territory ( 27 ), thereby allowing us to compare the approximate volume of individual chromosome copies. We found that the Xi-like chromosomes are significantly larger than the Xa-like chromosomes in IMR90 primed iPSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, G to I). The radius of gyration is a metric that approximates the radial size of the chromosome territory ( 27 ), thereby allowing us to compare the approximate volume of individual chromosome copies. We found that the Xi-like chromosomes are significantly larger than the Xa-like chromosomes in IMR90 primed iPSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The XIST RNA FISH probes that we used were the same as published before ( 27 ). Briefly, 50 probes were designed to target the XIST transcript.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the chromosome with a highly compact global structure has a more continuous structural landscape compared to the more specific and discrete states of the open and active chromosome. ( S8A , S8B and S8C Fig ) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such close proximity suggested that they may constitute a single Topologically Associating Domain (TAD) [ 62 ]; however, as investigated via TAD Knowledge Base (TADKB), they are a part of two adjacent TADs ( Figure 8 C and Figure S2 ). Although DNA sequences of single TAD interact more frequently than those from neighboring domains [ 63 ], adjacent TADs were also found to partially overlap [ 64 ], which provides a snippet of information on how AP-2δ targets might be organized in the genome.…”
Section: Resultsmentioning
confidence: 99%